(untitled) (American Journal of Business Management, Economics and Banking, 2025)
This article discusses the normative legal protection and specifics of ownership and entrepreneurial activity in Uzbekistan. The socio-economic development strategy implemented in Uzbekistan is attracting domestic and foreign investment by creating a favorable business and investment climate, achieving a strong development of the ownership sector